Exploring the capacity of the Somaliland healthcare system to manage female genital mutilation / cutting-related complications and prevent the medicalization of the practice: a cross-sectional study - Mohamed Yussuf; Dennis J. Matanda; Richard A. Powell (BMC, 2020)
Abstract Background Female genital mutilation/cutting (FGM/C) negatively impacts the wellbeing of girls and women throughout their lifecycle. In Somalia, FGM/C prevalence is nearly universal (98%) among females aged 15-49 years, with infibulation prevalence at 77%. Whilst there is need to engage healthcare workers in the prevention and management of FGM/C, minimal information exists indicating healthcare systems' capacity to fulfil this role. This study explored factors impacting the capacity of the Somaliland healthcare system to prevent the medicalization, and manage the complications of, FGM/C. Methods A cross-sectional qualitative study using semi-structured key informant interviews, conducted in the Somali language, was undertaken in the Maroodi Jeex and Awdal regions of Somaliland, in rural and urban Borama and Hargeisa districts in December 2016. A total of 20 interviews were conducted with healthcare workers comprised of medical doctors, nurses, midwives and system administrators. Transcribed and translated interview data were analysed using the template analysis approach. Results Healthcare workers reported understanding the adverse impact of FGM/C on the health of girls and women. However, they faced multiple contextual challenges in their preventative and management roles at the individual level, e.g., they lacked specific formal training on the prevention and management of FGM/C complications and its medicalization; institutional level, e.g., many facilities lacked funding and equipment for effective FGM/C management; and policy level, e.g., no national policies exist on the management of FGM/C complications and against its medicalization. Conclusion Healthcare systems in urban and rural Somaliland have limited capacity to prevent, diagnose and manage FGM/C. There is a need to strengthen healthcare workers' skill deficits through training and address gaps in the health system by incorporating the care of girls and women with FGM-related complications into primary healthcare services through multi-sectoral collaboration and coordination, establishing clinical guidelines for FGM/C management, providing related equipment, and enacting policies to prevent the medicalization of the practice.